The interactive effect of microstructure and stress state on the microscopic damage development of aluminum alloy tailor-welded blank. (August 2020) - Xing, L.; Zhan, M.; Gao, P.F.; Li, M.; Dong, Y.D.; He, W.W.
Abstract: Ductile fracture is the most common defect in plastic forming of tailor-welded blank (TWB). Revealing the damage and fracture characteristics of welded joint is very critical for accurately predicting the fracture defect. In this study, the fracture strain and microscopic damage development of a 2219 aluminum alloy welded joint were systemically investigated by in-situ-SEM testing. The interactive effects of microstructure and stress state on void growth and coalescence were quantitatively explored. Further, a micromechanical model based on actual microstructure was established to reveal the underlying mechanisms. The results show that the prominent void growth rates are affected by the particle size, particle volume fraction and grain size, and the effects vary with the stress triaxiality. The growing voids coalesce through one or both of ligament necking and shearing, which compete with each other dependent on the microstructure and stress state, making the variations of critical void spacing ratio. Attributing to these effects, the fracture strains of different microstructures in welded blank under various stress states are different, and the relationship between the fracture strain and microstructure relies on the stress state. These damage and fracture rules are explained by the microscopic heterogeneous deformation characteristics under different microstructures and stress states. Graphical abstract: Unlabelled Image Highlights: Damage and fracture behaviour vary with gradient microstructure and stress state for Al alloy tailor-welded blank. Void growth is dominated by the particle-cracking and matrix-cracking voids. Growth rates depend on the particle size and volume fraction and grain size, and the dependences vary with stress triaxiality. Ligament necking and shearing coexist and compete with each other dependent on the microstructure in void coalescence. These damage and fracture rules are explained by the microscopic heterogeneous deformation characteristic.